Force Distribution in the Canine Proximal Radio-Ulnar Joint on Extension of the Carpal Joint: A Cadaveric Study - Martin, Stephen A.; Kirby, Barbara M.; Kelly, Gabrielle; Gilchrist, Michael D.; Milgram, Joshua (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to measure the load on the lateral and medial aspects of the proximal radio-ulnar joint during extension of the carpus.Study Design This was an exvivo biomechanical study.Sample Population Twenty-two cadaveric Greyhound thoracic limbs were used.Methods Twenty-two paired thoracic limbs were used. The olecranon was attached to a custom jig with the foot resting on a stationary anvil. Load sensors were inserted into the proximal radio-ulnar joint, between the radial head and the lateral coronoid process, and between the radial head and the medial coronoid process. Specimens were tested under compression with measurements taken at 0, 4, 9 and 13.5 mm of axial displacement. Data collected at each point included forces on the specimen and medial and lateral coronoid processes as well as the angle of carpal joint extension.Results A linear mixed effects model relating load on the specimen and carpal joint extension angle had an R-squared value of 0.66, and load at the level of the medial coronoid process and angle of carpal extension had an R-squared value of 0.61. There was a significant difference in the loads measured on the lateral and medial coronoid processes at all angles (p < 0.0001).Conclusion Extension of the carpus results in asymmetric loading of the proximal radio-ulnar joint.Clinical Significance The findings of this study show that loading of the medial coronoid process may be more complex than originally thought and supports the future investigation of novel management and therapeutic options for affected patients.
Keywords: elbow; elbow dysplasia; biomechanics of joints